Oat arabinoxylans and their potential glycemic index-lowering role: an in vitro study - Anna Barjuan Grau; Karthik Vishaal Mohan; Juscelino Tovar; José Alfredo Zambrano (International Journal of Food Properties, 2023)
Oat (Avena sativa) is a cereal crop rich in dietary fibers, which are generally considered beneficial for human health. The objective of this work was to investigate the in vitro starch digestibility-reducing effect of the flour of a high arabinoxylan (AX) content (6.1%) oat line obtained from a random mutagenized oat population, compared to the original variety as a reference. The effect of the oat flours was tested on gelatinized potato starch as a dietary starch model, using a digestion dialysis method to calculate the predicted Glycaemic Index (pGI). The high AX flour reduced the potato starch pGI to larger extent than the flour from the original line. The pGI-lowering effect of the AX in the mutant line was confirmed by its attenuation following pre-treatment of the flour with xylanase. The larger pGI-lowering effect of the high AX oat line suggested this type of mutant as a potential functional food/ingredient for better management of postprandial glycemic responses.